The Vertical Style in Franz Kafka - Martín Arnedo, Santiago (Revista de Filología Alemana, 2023)
The reproach that Kafka lacks narrative sense, insofar as the action of his novels or stories never seems to advance towards any goal or resolution of the plot, does not necessarily imply a negative character. The fact that practically his complete work consists of short stories or unfinished novels seems to corroborate this inability to sustain a plot. This circumstance is partly due to personal characteristics: excessive perfectionism or insecurity about his own worth, which led, as is well known, to the concealment of his work as a writer. But we can assess this in the opposite direction. What I call "vertical style" has to do with a whole conception of art, even of reality, which redeems the part as self-sufficient, as the fractal that reflects the whole on different scales. With the disturbing suspicion that there is no such whole.
Keywords: The Trial; Kafka; style; Judaism